Militer contre l’invisibilité ; mal représenter - Léo Manac'h (Terrains/Théories)
This article describes the construction of a media figure of the “ill migrant” by activists fighting for the right to stay in France for medical reasons. It is shown that this figure is created from compassionate and victimized representations inherited from post-colonial imaginaries. In a context of repressive migration policies and media saturation of the image of the “migrant”, I argue that the political strategy of seeking visibility no longer works. If many social movements are problematized as fighting against the social and political invisibilization that affects minority groups, the aim is to question the political effects of negative, stigmatizing visibility.